Ewolucja czasu wolnego na przestrzeni dziejów. Gry komputerowe jako współczesna forma wolnoczasowa - Polcyn, Sylwia (Biuletyn Historii Wychowania, 2018)
Against the background of civilizational development, the 21st century appears as a time of great opportunities of self-development and general progress but also as a time of various new leisure activities. Thanks to the society’s prosperity, as a consequence of scientific and technological research as well as technological progress, our lives have been improving on a daily basis, evolving towards “excellence”. A similar evolution has taken place in terms of leisure activities that have been known since antiquity. Some of them have slipped into oblivion, giving way to more interesting and controversial forms of leisure, including computer games. Computer games have become a part of our society; the role they have played in the 21st century is immense. Both children and teenagers are involved in this sort of pastime on a daily basis. To many of them, a day without their favourite game or virtual hero is hard to imagine. When asked about computer games, most adolescents will flood you with information on the subject. To children and teenagers, games are a source of lively colours, sounds and great opportunities. They offer a world beyond a child’s common experience. Games make a child feel needed. Most of all, computer games are more attractive and more easily accessible than other leisure activities.